Prognostic value of metastatic lymph node ratio as an additional tool to the TNM stage system in gastric cancer. Issue 7 (July 2015) - Wu, X.-J.; Miao, R.-L.; Li, Z.-Y.; Bu, Z.-D.; Zhang, L.-H.; Wu, A.-W.; Zong, X.-L.; Li, S.-X.; Shan, F.; Ji, X.; Ren, H.; Ji, J.-F.
Abstract Background Gastric cancer is one of most common malignancies in the world. Currently the prognostic prediction is entirely based on the TNM staging system. In this study, we evaluated whether metastatic lymph node ratio (rN) at the time of surgery would improve the prognostic prediction in conjunction with the TNM staging system. Methods This retrospective study includes 745 patients, who had been referred for surgery due to gastric cancer between 1995 and 2007 and had at least 15 lymph nodes examined at the time of surgery without preoperative treatment. Clinicopathologic features and overall survival were analyzed using univariate and multivariate modes to identify the risk factors for overall survival. Results Median overall survival of all patients analyzed is 57.8 months and 5-year overall survival is 49.5%. Tumor site, macroscopic type, pTNM stage, and rN stage are identified as independent prognostic factors. Increased positive lymph node ratio correlates with shorter survival in all patients and in each T and N stage. In stage III gastric cancer patients, rN stage shows additional prognostic value on overall survival (p < 0.001). Conclusions rN stage is a simple and promising prognostic factor of gastric cancer after surgery in addition to the TNM stage system especially in stage III patients. But the independent prognostic value of rN stage in stage I, II and IV gastric cancer is yet to be determined.